NASA’s hyperspectral EMIT mission improves invasive plant detection in Everglades National Park - Susan Meerdink; Drew Hiatt; Hillary Cooley; Alina Zare; S. Luke Flory (Biological Invasions, 2026)
Invasive plant species remain one of the largest threats to ecosystems, and a major limitation to predicting and managing invasives is the lack of updated and spatially relevant species distribution data. Remote sensing has emerged as an option for providing wall-to-wall mapping of species distributions, of which the most successful approaches employed hyperspectral imagery primarily limited to airborne platforms. We explore the newly launched hyperspectral Earth surface Mineral dust source InvesTigation (EMIT) mission on the International Space Station (ISS) to detect invasives compared to the multispectral satellites Sentinel-2, Landsat 8, PlanetScope SuperDove, and imagery from the National Agricultural Imagery Program (NAIP). We focused on detecting the presence of Brazilian peppertree ( Schinus terebinthifolia ) in Everglades National Park in February 2024 using a pixel-based support vector machine classifier, comparing spectral and spatial resolutions. With a 60 m spatial resolution and 223 spectral bands, EMIT imagery enhanced invader detection, achieving an average overall accuracy of 80.2% and captured the known distribution of Brazilian peppertree the best. Sentinel-2 resampled to 60 m spatial resolution had the next highest accuracy with 78.8%, but failed to capture the known distribution. The classifications show that additional spectral bands, rather than spatial size, yield improved results when detecting this shrub/small tree invader, especially at locations with lower invader density, which are often a target for Early Detection and Rapid Response (EDRR) management efforts. There is still spectral confusion, most likely due to the limited phenological differences between the invader and native communities at the time of year when the imagery was collected, which could be potentially overcome using imagery from the fall or time series. The most recent work detecting invasives using spaceborne hyperspectral imagery was concluded with the decommissioning of Hyperion in 2017, so the launch of EMIT revitalizes opportunities for plant invader detection from space. With the irregular orbit of the ISS, EMIT imagery may not capture key phenological events that would increase the spectral separation between invaders and native communities. However, optimally timed collection will be possible from future global hyperspectral missions due to consistent image revisit times, which will significantly improve detection capabilities by capturing the dynamic nature of invasives. This work showcases that the new wave of hyperspectral spaceborne sensors can improve invasive plant detection even at coarse spatial resolutions, and significantly improve detection for early detection and rapid response management efforts.

Population Genomics of a Cosmopolitan Weed Provides Insights Into Its Local Adaptation and Recent Demographic History - Marilia Souza Lucas; Christoph Rosche; Isabell Hensen; Stefan G. Michalski; Dávid U. Nagy; Diana Gamba; Renske E. Onstein; Karime Abidkulova; Mohammad Al‐Gharaibeh; Ali A. Al‐Namazi; Sirwan Babaei; Fernando Bastida; et al. (Molecular Ecology, 2026)
Invasive plant species present a growing ecological and economic challenge, and often adapt rapidly to their novel environments through complex demographic and evolutionary processes. Invasion genomics offers powerful tools to disentangle these processes, but most studies rely on geographically narrow sampling across native and non‐native ranges. Erigeron canadensis is a cosmopolitan weed native to North America that has successfully invaded diverse climates worldwide. We used double‐digest restriction site‐associated DNA sequencing (ddRADseq) to investigate the genetic diversity and structure of 280 E. canadensis populations across the Northern Hemisphere. We found that native and non‐native populations maintained comparable genetic diversity. Population structure analyses revealed four genetic clusters that were mainly differentiated along latitudinal and aridity gradients. However, one cluster was strongly overrepresented in the non‐native compared to the native range. In the native range, genetic differentiation was shaped by spatial and environmental gradients, while in non‐native regions human‐mediated dispersal and repeated introductions disrupted environmentally driven genetic structure. Migration network analyses revealed limited intercontinental connectivity and a possible role of long‐distance dispersal in within‐range expansions. Genomic offset analyses showed that genotype‐environment mismatches in non‐native populations associated with reduced growth and reproduction. Together, our results indicate that the invasion dynamics of E. canadensis were driven by multiple introductions, population admixture, and lineage sorting, while some genotypes contributed disproportionately to the spread of this invader. The presence of apparent maladaptation suggests that even long‐established invaders may still be evolving in response to their novel environment, raising concerns about potential future expansions.

Foliar pathogen epidemic slows decomposition of invasive plant litter - Brett R. Lane; Chris Wojan; Carlie Meehan; Amy E. Kendig; Robert D. Holt; Philip F. Harmon; Keith Clay; S. Luke Flory; Erica M. Goss (Ecology, 2026)
Decomposition of plant litter, facilitated primarily by microbial decomposers, plays a critical role in biogeochemical cycling and ecosystem function. The rate of litter decomposition can determine its environmental impact, where accelerated decomposition alters the timing and rate of nutrient release and may promote nutrient leaching, whereas slowed decomposition can result in litter accumulation, which impacts seedling recruitment, fire regimes, perennation of microbial communities, and slows nutrient release. Mutualistic endophytes are known to slow litter decomposition, but less is known about the impact that plant pathogens, present in diseased litter, have on decomposition rates. We compared litter decomposition of the invasive annual grass Microstegium vimineum with Bipolaris leaf spot symptoms, a fungal disease, to litter without symptoms of the disease in a year‐long common garden experiment. We found leaf tissue with disease symptoms decomposed later in the year compared to litter without symptoms. By summer, 54% of leaf tissue from healthy sites remained compared to 80% of leaf material from diseased litter. Fungal infection did not impact the lignin or C:N content of the litter. There were significant differences in fungal community composition between infected and healthy litter at the start of the experiment that persisted until the end of summer. Disease epidemics prior to senescence contributed to the persistence of infected tissue, which could slow the return of nutrients to the environmental pool and promote the survival and dispersal of pathogen inoculum the following season.

Mechanistic pathways of tick exposure risk in native and invaded plant communities - Drew Hiatt; Whalen W. Dillon; Allison Gardner; Steven Cabrera; Michael Dietze; Brian F. Allan; S. Luke Flory (Ecology, 2025)
Plant invasions may alter disease vector abundance by several mechanistic pathways, including modifying microclimates that influence vector survival or changing habitats to influence host use. Here, we used a field experiment and observational data to evaluate multiple mechanistic pathways (tick survival and host abundance) by which plant invasions may alter vector‐borne disease risk using the common disease vector lone star tick ( Amblyomma americanum ), its preeminent host white‐tailed deer ( Odocoileus virginianus ), and the widespread invasive cogongrass ( Imperata cylindrica ) in the southeastern United States. In the field experiment, ticks survived over 50% longer in areas dominated by the invasive plant compared to those with only native plant species. Invaded areas had lower temperatures and higher relative humidity, yielding a lower vapor pressure deficit (VPD) that likely reduced tick desiccation. The observational study showed similar average tick abundance in native and invaded plant communities and no difference in wildlife host (white‐tailed deer) activity between plant communities. However, there was a positive relationship between tick abundance and white‐tailed deer activity, but only in native areas. Together, these results suggest that more favorable microclimate conditions resulting in greater tick longevity are the dominant driver of tick abundance in invaded areas, while tick abundance in native‐dominated areas may be promoted, at least in part, by white‐tailed deer activity. Our results demonstrate that plant invasions can affect multiple, potentially counteracting mechanistic pathways that contribute to tick exposure risk. The complexity of these relationships highlights the need for a better understanding of how invasive species and other global change drivers influence disease vectors and, ultimately, disease transmission.

Impacts of Weather Anomalies and Climate on Plant Disease - Devin Kirk; Jeremy M. Cohen; Vianda Nguyen; Marissa L. Childs; Johannah E. Farner; T. Jonathan Davies; S. Luke Flory; Jason R. Rohr; Mary I. O'Connor; Erin A. Mordecai (Ecology Letters, 2025)
Predicting the effects of climate change on plant disease is critical for protecting ecosystems and food production. Here, we show how disease pressure responds to short‐term weather, historical climate and weather anomalies by compiling a global database (4339 plant–disease populations) of disease prevalence in both agricultural and wild plant systems. We hypothesised that weather and climate would play a larger role in disease in wild versus agricultural plant populations, which the results supported. In wild systems, disease prevalence peaked when the temperature was 2.7°C warmer than the historical average for the same time of year. We also found evidence of a negative interactive effect between weather anomalies and climate in wild systems, consistent with the idea that climate maladaptation can be an important driver of disease outbreaks. Temperature and precipitation had relatively little explanatory power in agricultural systems, though we observed a significant positive effect of current temperature. These results indicate that disease pressure in wild plants is sensitive to nonlinear effects of weather, weather anomalies and their interaction with historical climate. In contrast, warmer temperatures drove risks for agricultural plant disease outbreaks within the temperature range examined regardless of historical climate, suggesting vulnerability to ongoing climate change.

Development and application of a second-generation multilingual tool for invasion risk screening of non-native terrestrial plants - Lorenzo Vilizzi; Marina Piria; Dariusz Pietraszewski; Daniela Giannetto; S. Luke Flory; Gábor Herczeg; Hayrünisa Baş Sermenli; Mihaela Britvec; Ilona Jukoniene; Lukas Petrulaitis; Ivana Vitasović-Kosić; David Almeida; et al. (Science of The Total Environment, 2024)

Trade‐offs in non‐native plant herbivore defences enhance performance - Xiao Sun; Yumei Sun; Xueyao Cao; Xincong Zhai; Ragan M. Callaway; Jinlong Wan; S. Luke Flory; Wei Huang; Jianqing Ding (Ecology Letters, 2023)
Non‐native plants are typically released from specialist enemies but continue to be attacked by generalists, albeit at lower intensities. This reduced herbivory may lead to less investment in constitutive defences and greater investment in induced defences, potentially reducing defence costs. We compared herbivory on 27 non‐native and 59 native species in the field and conducted bioassays and chemical analyses on 12 pairs of non‐native and native congeners. Non‐natives suffered less damage and had weaker constitutive defences, but stronger induced defences than natives. For non‐natives, the strength of constitutive defences was correlated with the intensity of herbivory experienced, whereas induced defences showed the reverse. Investment in induced defences correlated positively with growth, suggesting a novel mechanism for the evolution of increased competitive ability. To our knowledge, these are the first linkages reported among trade‐offs in plant defences related to the intensity of herbivory, allocation to constitutive versus induced defences, and growth.

Moving scholarship on invasion science forward - Julie L. Lockwood; Deah Lieurance; S. Luke Flory; Laura A. Meyerson; Anthony Ricciardi; Dan Simberloff (Trends in Ecology & Evolution, 2023)

Research gaps limit understanding of invasion-fire cycles - Giovanna Tomat-Kelly; S. Luke Flory (Biological Invasions, 2023)

Interacting global change drivers suppress a foundation tree species - S. Luke Flory; Whalen Dillon; Drew Hiatt (Ecology Letters, 2022)
Ecological stress caused by climate change, invasive species and anthropogenic disturbance is driving global environmental change, but how these stressors interact to impact native species are poorly understood. We used a field experiment to test how two stressors (drought and plant invasion by Imperata cylindrica ) interacted to determine the effects of a third stressor (fire) on a foundation tree species ( Pinus palustris ). The invasion combined with prolonged drought resulted in shorter trees than invasion alone. The invasion also resulted in 65% greater fuel loads, four times taller flames, greater maximum temperatures and longer heating duration. Consequently, nearly all tree mortality occurred due to a synergistic interaction between the drought + invasion treatment and fire, where invasion caused taller flames that impacted trees that were shorter due to drought. These findings demonstrate that synergy amongst ecological stressors can dramatically impact native species, with significant implications for forecasting the effects of multiple stressors under global change.

Domestication does not alter invasion risk of a non-native legume - Tabitha Petri; Brian Rehill; Deah Lieurance; S. Luke Flory (Oecologia, 2021)

Potential effects of domestication on non-native plant invasion risk - Tabitha Petri; Susan Canavan; Doria R. Gordon; Deah Lieurance; S. Luke Flory (Plant Ecology, 2021)

Keys to enhancing the value of invasion ecology research for management - Jennifer L. Funk; Ingrid M. Parker; Virginia Matzek; S. Luke Flory; Erik T. Aschehoug; Carla M. D’Antonio; Wayne Dawson; Diane M. Thomson; Justin Valliere (Biological Invasions, 2020)

Global change stressors alter resources and shift plant interactions from facilitation to competition over time - Christina Alba; Catherine Fahey; S. Luke Flory (Ecology, 2019)
Global change stressors such as drought and plant invasion can affect ecosystem structure and function via mediation of resource availability and plant competition outcomes. Yet, it remains uncertain how native plants respond to drought stress that co‐occurs with potentially novel resource conditions created by a nonnative invader. Further, there is likely to be temporal variation in competition outcomes between native and nonnative plant species depending on which resources are most limiting at a given time. Interacting stressors coupled with temporal variation make it difficult to predict how global change will impact native plant communities. To address this knowledge gap, we conducted a 5‐yr factorial field experiment to quantify how simulated drought, plant invasion (by cogongrass, Imperata cylindrica ), and these stressors combined, affected resource availability (soil moisture and light) and competition dynamics between the invader and native longleaf pine ( Pinus palustris ), a foundation species in southeast U.S. forests. Drought and invasion mediated the survival and performance of pine seedlings in temporally dynamic and unexpected ways. Drought and invasion alone each significantly reduced pine seedling survival. However, when the stressors occurred together, the invader offset drought stress for pine seedlings by maintaining high levels of soil moisture, humidity, and shade compared to uninvaded vegetation. This facilitative effect was pronounced for 2 yr, yet shifted to strong competitive exclusion as the invasion progressed and the limiting resource switched from soil moisture to light. After 3 yr, pine tree survival was low except for pines growing with uninvaded vegetation under ambient precipitation conditions. After 5 yr, pines experiencing a single stressor were taller and had greater height to diameter ratios than pines under no stress or both stressors. This outcome revealed a filtering effect where poorly performing trees were culled under stressful conditions, especially when pines were growing with the invader. Together, these results demonstrate that although drought and invasion suppressed a foundation tree species, the invader temporarily moderated stressful drought conditions, and at least some trees were able to survive despite increasingly strong competition. Such unpredictable effects of interacting global change stressors on native plant species highlight the need for additional long‐term studies.

Grass invasion and drought interact to alter the diversity and structure of native plant communities - Catherine Fahey; Christine Angelini; S. Luke Flory (Ecology, 2018)
Understanding the interactive effects of species invasions and climate change is essential for predicting future shifts in biodiversity. Because multiple stressors can interact in synergistic or antagonistic ways, it is notoriously difficult to anticipate their combined effects on species assemblages. However, some hypotheses predict that plant invasions will become increasingly problematic as climate change improves conditions for invaders or lowers the biotic resistance of native communities. In a 4‐yr field experiment, we quantified the individual and interactive effects of invasion by a globally problematic C 4 grass, Imperata cylindrica , and chronic simulated drought imposed by rainout shelters on the whole plant communities of regenerating longleaf pine forest. Invasion both inhibited plant colonization and enhanced plot‐level extinctions, resulting in a severe (60%) loss of plant diversity across all functional groups, including perennial grasses and forbs, annual forbs, and woody species and dramatic shifts in community composition. Experimental drought reduced diversity by 20%, and caused a shift in the dominant functional groups, but had no significant effect on cover of the invader. The invader partially ameliorated water stress in the drought treatment such that invaded plots had higher soil moisture than uninvaded plots. Consequently, the combined effects of invasion and drought were lower than expected from an additive model of multiple stressors. These findings, which may have broader implications for how other C 4 grass invaders will interact with drought to shift native community dynamics, challenge the perception that climate change will exacerbate invasions. In revealing that invasive species pose a major threat to the diversity and structure of native communities despite their moderating effects on abiotic stress, this work also highlights that management of aggressive invaders may be critical to preserving biodiversity regardless of future climate.

Grazing enhances belowground carbon allocation, microbial biomass, and soil carbon in a subtropical grassland - Chris H. Wilson; Michael S. Strickland; Jack A. Hutchings; Thomas S. Bianchi; S. Luke Flory (Global Change Biology, 2018)
Despite the large contribution of rangeland and pasture to global soil organic carbon ( SOC ) stocks, there is considerable uncertainty about the impact of large herbivore grazing on SOC , especially for understudied subtropical grazing lands. It is well known that root system inputs are the source of most grassland SOC , but the impact of grazing on partitioning of carbon allocation to root tissue production compared to fine root exudation is unclear. Given that different forms of root C have differing implications for SOC synthesis and decomposition, this represents a significant gap in knowledge. Root exudates should contribute to SOC primarily after microbial assimilation, and thus promote microbial contributions to SOC based on stabilization of microbial necromass, whereas root litter deposition contributes directly as plant‐derived SOC following microbial decomposition. Here, we used in situ isotope pulse‐chase methodology paired with plant and soil sampling to link plant carbon allocation patterns with SOC pools in replicated long‐term grazing exclosures in subtropical pasture in Florida, USA . We quantified allocation of carbon to root tissue and measured root exudation across grazed and ungrazed plots and quantified lignin phenols to assess the relative contribution of microbial vs. plant products to total SOC . We found that grazing exclusion was associated with dramatically less overall belowground allocation, with lower root biomass, fine root exudates, and microbial biomass. Concurrently, grazed pasture contained greater total SOC , and a larger fraction of SOC that originated from plant tissue deposition, suggesting that higher root litter deposition under grazing promotes greater SOC . We conclude that grazing effects on SOC depend on root system biomass, a pattern that may generalize to other C4‐dominated grasslands, especially in the subtropics. Improved understanding of ecological factors underlying root system biomass may be the key to forecasting SOC and optimizing grazing management to enhance SOC accumulation.

Plant community composition and structural characteristics of an invaded forest in the Galápagos - Gonzalo Rivas-Torres; S. Luke Flory; Bette Loiselle (Biodiversity and Conservation, 2018)

Long-term studies are needed to reveal the effects of pathogen accumulation on invaded plant communities - S. Luke Flory; Christina Alba; Keith Clay; Robert Holt; Erica Goss (Biological Invasions, 2018)

Emerging pathogens can suppress invaders and promote native species recovery - S. Luke Flory; Christina Alba; Keith Clay; Robert D. Holt; Erica M. Goss (Biological Invasions, 2018)

Predicted versus actual invasiveness of climbing vines in Florida - Doria R. Gordon; Deah Lieurance; S. Luke Flory (Biological Invasions, 2017)

Propagule quality mediates invasive plant establishment - James A. Estrada; Chris H. Wilson; Julienne E. NeSmith; S. Luke Flory (Biological Invasions, 2016)

Emergence and accumulation of novel pathogens suppress an invasive species - Kerry Bohl Stricker; Philip F. Harmon; Erica M. Goss; Keith Clay; S. Luke Flory (Ecology Letters, 2016)
Emerging pathogens are a growing threat to human health, agriculture and the diversity of ecological communities but may also help control problematic species. Here we investigated the diversity, distribution and consequences of emerging fungal pathogens infecting an aggressive invasive grass that is rapidly colonising habitats throughout the eastern USA . We document the recent emergence and accumulation over time of diverse pathogens that are members of a single fungal genus and represent multiple, recently described or undescribed species. We also show that experimental suppression of these pathogens increased host performance in the field, demonstrating the negative effects of emerging pathogens on invasive plants. Our results suggest that invasive species can facilitate pathogen emergence and amplification, raising concerns about movement of pathogens among agricultural, horticultural, and wild grasses. However, one possible benefit of pathogen accumulation is suppression of aggressive invaders over the long term, potentially abating their negative impacts on native communities.

Bioenergy Feedstocks at Low Risk for Invasion in the USA: a “White List” Approach - Lauren D. Quinn; Doria R. Gordon; Aviva Glaser; Deah Lieurance; S. Luke Flory (BioEnergy Research, 2015)

Combining mesocosm and field experiments to predict invasive plant performance: a hierarchical Bayesian approach - Chris H. Wilson; T. Trevor Caughlin; David J. Civitello; S. Luke Flory (Ecology, 2015)
Invasive plant fecundity underlies propagule pressure and ultimately range expansion. Predicting fecundity across large spatial scales, from regions to landscapes, is critical for understanding invasion dynamics and optimizing management. However, to accurately predict fecundity and other demographic processes, improved models that scale individual plant responses to abiotic drivers across heterogeneous environments are needed. Here we combine two experimental data sets to predict fecundity of a widespread and problematic invasive grass over large spatial scales. First, we analyzed seed production as a function of plant biomass in a small‐scale mesocosm experiment with manipulated light levels. Then, in a field introduction experiment, we tracked plant performance across 21 common garden sites that differed widely in available light and other factors. We jointly analyzed these data using a Bayesian hierarchical model (BHM) framework to predict fecundity as a function of light in the field. Our analysis reveals that the invasive species is likely to produce sufficient seed to overwhelm establishment resistance, even in deeply shaded environments, and is likely seed‐limited across much of its range. Finally, we extend this framework to address the general problem of how to scale up plant demographic processes and analyze the factors that control plant distribution and abundance at large scales.

Competitive and allelopathic effects of the invasive shrub Schinus terebinthifolius (Brazilian peppertree) - Katherine Nickerson; S. Luke Flory (Biological Invasions, 2015)

Positive feedbacks to growth of an invasive grass through alteration of nitrogen cycling - Marissa R. Lee; S. Luke Flory; Richard P. Phillips (Oecologia, 2012)

Competitive context alters plant–soil feedback in an experimental woodland community - Sarah Shannon; S. Luke Flory; Heather Reynolds (Oecologia, 2012)

Potential for endophyte symbiosis to increase resistance of the native grass Poa alsodes to invasion by the non-native grass Microstegium vimineum - Skylar Craig; Sonia Kannadan; S. Luke Flory; Elizabeth K. Seifert; Kenneth D. Whitney; Jennifer A. Rudgers (Symbiosis, 2011)

Non-native grass invasion suppresses forest succession - S. Luke Flory; Keith Clay (Oecologia, 2010)

Non-native grass invasion alters native plant composition in experimental communities - S. Luke Flory; Keith Clay (Biological Invasions, 2010)

Variation for phenotypic plasticity among populations of an invasive exotic grass - Tyler Droste; S. Luke Flory; Keith Clay (Plant Ecology, 2010)

Response of host plants to periodical cicada oviposition damage - S. Luke Flory; W. Brett Mattingly (Oecologia, 2008)

Invasive shrub distribution varies with distance to roads and stand age in eastern deciduous forests in Indiana, USA - S. Luke Flory; Keith Clay (Plant Ecology, 2006)